Pengaruh Program Dewan Kemakmuran Masjid (DKM) terhadap Minat Remaja dalam Memakmurkan Masjid Al-Muttaqin Desa Bumi Mulya - Aprizal Aprizal (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
The observation that less than 50% of youth are involved in DKM programs shows a significant social shift. This study has a strategic objective to explore in depth the role of DKM Al-Muttaqin in efforts to generate religious fervor and participation of the younger generation. This research is quantitative with survey method. The population was all teenagers with random sampling technique. Data collection used observation, questionnaires, and interviews. The analysis technique is simple linear regression. The results showed that the Al-Muttaqin DKM program was in the moderate category or 69.23%, and teenagers' interest in the DKM program was also in the moderate category with the same proportion. This study found a significant influence between the DKM program and teenagers' interest, as evidenced by the correlation value r_(xy) of 0.292, where the factors that influence teenagers' interest include activities such as congregational prayers, the implementation of Islamic Holidays (PHBI), joint religious activities, community service to clean the mosque, and joint Al-Qur'an reading activities that can include teenagers in the DKM program.